Hypothyroidism in polycystic ovarian syndrome: a comparative study of clinical characteristics, metabolic and hormonal parameters in euthyroid and hypothyroid polycystic ovarian syndrome women - SJ, Ramanand; GT, Raparti; NR, Halasawadekar; JB, Ramanand; AV, Kumbhar; RD, Shah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was conducted to examine influence of hypothyroidism on pathophysiology and features of PCOS with respect to clinical characteristics of polycystic ovarian syndrome (PCOS), hormonal and metabolic profile. Methods: 102 euthyroid PCOS and 18 hypothyroid PCOS women were included in this cross-sectional study after considering inclusion and exclusion criteria. The study subjects were assessed for various signs and symptoms like recent weight gain, obesity, abnormal hair growth, hirsutism, hair loss, acne, acanthosis nigricans and infertility. Various hormonal and metabolic parameters were evaluated viz. Luteinizing hormone, Follicle stimulating hormone, LH:FSH ratio, testosterone, prolactin, dehydroepiandrosterone, fasting insulin and fasting blood glucose. BMI and HOMA values were calculated. Results: Association of hirsutism, excessive hair growth, hair loss, acanthosis nigricans, acne, infertility was not significant between the two groups. Majority of patients in both the groups were overweight/obese. BMI and number of patients complaining weight gain was significantly more in hypothyroid PCOS women. While no statistical difference in LH, FSH, LH:FSH ratio, prolactin, and testosterone levels was found, serum DHEA level was significantly less in hypothyroid PCOS group. No statistical difference in fasting blood glucose and insulin levels was found between the two groups. Though both the groups show insulin resistance, HOMA values were significantly more in hypothyroid PCOS women. Conclusions: Presence of hypothyroidism significantly increased severity of insulin resistance as well as obesity in PCOS. This could have adverse metabolic consequences in them. Concurrent occurrence of both these disorder could also possibly affect other features of the PCOS viz. hair loss and infertility.